Pengembangan Media Pembelajaran Berbasis Hypertext pada Komunikasi Data dan Jaringan Komputer Berorientasi Konsep Subak - Ketut Agustini (JTP - Jurnal Teknologi Pendidikan, 2015)
This study aimed to develop a hypertext-based learning media for data com- munication and computer networks in Subak concept oriented. The method used an R & D to design development Dick & Carey model of the modi ed software with a special method Software Development Life Cycle. In order to be validated in the academic and scienti c, the resulting software have tested through three stages of testing, namely testing as a soft- ware engineering, testing as a medium of learning and eld trials to test the effectiveness by using a quasi-experimental posttest-only control-group design to students majoring in engineering education informatics . The results showed that effective instructional media used to increase the level of student mastery of the material, and the student response was very positive.